The relational aspect of upbringing in view of the relationship between the marital relationship and the perception of the reality of upbringing in the family - Opozda, Danuta (Karkonoska Państwowa Szkoła Wyższa, 2012)
In the article, the problem of the relational aspect of upbringing is presented. It is based on the assumptions of the system theory of the family and the theory of social schemes as well as the results of the author’s research on the importance of the quality of the marital relationship in the upbringing of a child in the family. The present paper supports the thesis that upbringing a child in the family takes place in a system of intra-familial relationships and that its relational aspect is expressed in numerous areas.
Keywords: relations; upbringing; marriage; family